United Republic of Tanzania : Financial System Stability Assessment-Press Release; Staff Report; and Statement by the Executive Director for the United Republic of Tanzania. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
Tanzania's bank-dominated financial sector is small, concentrated, and at a relatively nascent stage of development. Financial services provision is dominated by commercial banks, with the ten largest institutions being preeminent in terms of mobilizing savings and intermediating credit. Medium-to-small banks rely systematically more on costlier, short-term, interbank financing and institutional deposits and have markedly higher operating costs. These structural features underpin financial stability challenges which are significant. Bank asset quality has deteriorated sharply in recent years, and under-provisioning is significant, belying the apparently comfortable capital cushions. Credit growth has fallen precipitously, corporate debt loads have risen, and their cash flows are weak. Dollarization of bank balance-sheets raises the possibility of solvency stress under shocks being exacerbated by funding liquidity pressures, especially at smaller banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet